Information and software technologies : 23rd International Conference, ICIST 2017, Druskininkai, Lithuania, October 12-14, 2017, proceedings /: 23rd International Conference, ICIST 2017, Druskininkai, Lithuania, October 12-14, 2017, proceedings. (2017) - Unknown
No abstract available